The words of the Holy Qurʾān and Their Renewed Meanings: Kata-kata dalam Al-Qur'ān dan Makna yang Diperbaharui - Al-Balushi, Rashid (Aqwal: Journal of Qur'an and Hadis Studies, 2024)
Background and Objectives: This study emerges from the need to understand semantic shifts in the Qurʾān more comprehensively, particularly for the terms “qāʾil” and “al-Amānah,”. The main objective is to show that the words of the Holy Qurʾān may acquire new meanings or usages, based on various factors, and that the expanded meanings of Qurʾānic words have implications for the overall understanding of the respective verses. The methodology involves reference to classical and modern lexicons, as well as contextual inquiries grounded in tafsīr literature. The data were analyzed qualitatively by integrating different perspectives.  The main results: “qāʾil,” commonly understood as “one who speaks,” may also refer to “one at midday,” while “al-Amānah” does not necessarily refer to “material trusts or religious rites," but also to the "human intellect and the obligation to exercise it to find God" based on the evidence for the existence of God. These semantic developments pave the way for a richer and more responsive understanding of the Qurʾān, resonating with current scholarly discourse. Contribution, this research proposes an integrative “textual-contextual” approach that highlights semantic, historical, and scientific elements. Such a framework can enrich scholars’ efforts in interpreting Qurʾānic verses and relating them to social realities and advances in knowledge. Conclusion, the expanded meanings of these two terms affirm that Qurʾānic interpretation is dynamic. By considering linguistic, historical, and modern contexts, this study offers fresh insights that bring the Qurʾān closer to contemporary understanding, without dismissing the enduring value of classical tafsīr.